Correlation of Diffusion-weighted MR imaging and FDG PET/CT in the Diagnosis of Metastatic Lymph Nodes of Head and Neck Malignant Tumors - Şahin, Şamil; Duymaz, Yaşar Kemal; Erkmen, Burak; Karabulut, Burak; Deveci, İldem; Sürmeli, Mehmet; Şahin Yılmaz, Aslı; Semiz Oysu, Aslıhan; Oysu, Çağatay (European Journal of Therapeutics, 2023)
Objectives: The aim of this study was to investigate the efficacy of DW-MRI as a reliable imaging modality for detecting metastatic neck lymph nodes of head and neck SCC. Methods: 32 patients underwent FDG PET/CT and diffusion-weighted MRI were evaluated. Histopathologic analysis of lymph node metastases was used as the gold standard for assessment. We analyzed differences in sensitivity, specificity, accuracy, positive predictive value and negative predictive value among the imaging modalities using the Chi-square test. Their discriminative power evaluated using the Receiver-Operating Characteristic curve and calculation of the area under the curve. The correlation between ADCmin and SUVmax was calculated using the Spearman test. SPSS 24 was used for statistical analyses. P value of 0.05 indicates a statistically significant difference. Results: A total of 32 patients with 50 neck dissections with head and neck SCC included. Sensitivity, specificity, accuracy, positive and negative predictive value of neck palpation was %72, %60, %70, %62 and %80 respectively. Sensitivity, specificity, accuracy, positive and negative predictive value of DW-MRI was %87,5, %96,2, %92, %95,5 and %89,3 respectively, according to ADCmin cutoff value 0.82×10-3s/mm2 . Sensitivity, specificity, accuracy, positive and negative predictive value of FDG-PET/CT was %91,7, %100, %96, %100 and %92,9 , respectively ,according to SUVmax cutoff value 3.4. For all neck dissections, there was a statistically significant inverse correlation between ADCmin and SUVmax (P<001). Conclusion: DW-MRI is reliable as detecting cervical lymph node metastases as FDG-PET/CT. DWI and FDG PET/CT could play a complementary role in clinical assessment. The original version of this article, unfortunately contained an error. The name of Aslıhan Semiz Oysu, who is one of the co-authors and took part in every stage of the study, was not inadvertently added to the author list by the corresponding author. The author apologizes for this confusion. Given in this article are the correct author names. Correction to: https://doi.org/10.58600/eurjther1878